(untitled) (LEARNing Landscapes, 2015)
Using a narrative inquiry approach, the author examines how children, teachers, and parents benefit from the practice of conducting home visits. The author reflects on her own research and practice and imagines possibilities for enhancing parent engagement through home visiting. Central to this paper is how the knowledge gained from families through home visits can be used to enrich curriculum and create an inclusive learning environment in the classroom. Suggestions on how to help break down the barriers teachers and administrators face in planning for and conducting home visits are discussed.